Engineering Societies in the Agents World X 10th International Workshop, ESAW 2009, Utrecht, The Netherlands, November 18-20, 2009, Proceedings - Aldewereld, Huib; Dignum, Virginia; Picard, Gauthier (Lecture Notes in Artificial Intelligence,, 2009)
This book constitutes the refereed proceedings of the 10th International Workshop on Engineering Societies in the Agents World, ESAW 2009, held in Utrecht, The Netherlands, in November 2009. The 13 revised full papers and 5 short contributions presented together with two invited talks were carefully selected from 31 submissions. The papers are organized in topical sections on self-organization, software-engineering and architectures, social aspects of agent societies, organization and autonomy. This proceedings concludes with the extended abstracts of 6 contributions to a demonstration session on agent-based technologies and works.